Resilience in Families of Children with Special Needs from Sibling’s Perspective - Indarwati, Retno; Lusdiana, Ika; Mishbahatul, Eka; Wahyuni , Sylvia Dwi; Fitryasari, Rizki; Rahmawati, Apriana (International Journal of Psychosocial Rehabilitation, 2020)
Family resilience is a dynamic process in the family to make positive adaptations to the danger from outside and from within the family. The purpose of this study was to describe the family resilience in families with special needs children from the perspective of siblings. This was a qualitative research design phenomenological approach with in-depth interview method on 15 siblings of children with special needs. The population was the siblings of children with special needs who were registered at the Gresik Resource Center. Participants were teenage siblings of children with special needs who live in the same house. Data were collected by visiting the participant's home. This study used data collection with purposive sampling. The level of family resilience was strongly influenced by the relationship, level or sequence of birth positions within the brotherhood, and various responses of the siblings of the child with special needs. The positive response generated will strengthen the communication process, the division of tasks and obligations in accordance with the role in the family belief system that can produce better family resilience. It is hoped that this research could be the basis for further research and could be a model of community nursing intervention, especially families with child with special needs, such as the establishment of sibling communities of children with special needs in Indonesia by involving related institutions.